2015
DOI: 10.1097/bpo.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Long-arm Casting Versus Double–Sugar-Tong Splinting of Acute Pediatric Distal Forearm Fractures

Abstract: Level II-prospective, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…Furthermore, recent reports from Wendling-Keim et al [13] and Roth et al [14] have shown that the guidelines regarding acceptable angulation that we have followed might have been too strict and that even larger angulations do not result in poor outcomes. The rate of secondary displacements in our study (31% of patients experienced a secondary displacement, whereas 20% required a secondary procedure) is comparable with recent reports by Levy et al [15] (33% with secondary displacement), Khandekar et al [10] (45% with secondary displacement) and Wendling-Keim et al [13] (14.5% of patients requiring a secondary procedure). We believe that these facts justify our conservative strategy in the initial treatment of displaced distal forearm fractures in children.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, recent reports from Wendling-Keim et al [13] and Roth et al [14] have shown that the guidelines regarding acceptable angulation that we have followed might have been too strict and that even larger angulations do not result in poor outcomes. The rate of secondary displacements in our study (31% of patients experienced a secondary displacement, whereas 20% required a secondary procedure) is comparable with recent reports by Levy et al [15] (33% with secondary displacement), Khandekar et al [10] (45% with secondary displacement) and Wendling-Keim et al [13] (14.5% of patients requiring a secondary procedure). We believe that these facts justify our conservative strategy in the initial treatment of displaced distal forearm fractures in children.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was no difference between groups at cast removal. 23 In the current study, only 19% of fractures with unacceptable alignment at follow-up underwent operative intervention, and the average age of those patients was 15.7 years compared with 8.7 years for patients with unacceptable alignment who did not receive interventions. It has been suggested that reluctance to perform remanipulation for younger patients with malaligned both bone forearm fractures was influenced by remaining growth potential to correct residual deformities.…”
Section: Discussionmentioning
confidence: 54%
“…A possible explanation for this finding is poor immobilization with the use of a sugar-tong splint and fiberglass overwrap before conversion to a short arm cast. Levy et al 23 performed a prospective randomized trial comparing maintenance of reduction for distal radius and distal both bone forearm fractures with either a long arm cast or a sugar-tong splint converted to a short arm cast after 1 week. They found better postreduction alignment, less loss of reduction, and less need for remanipulation with sugar-tong splints.…”
Section: Discussionmentioning
confidence: 99%
“…1 Presence of tough periosteum and continued remodelling makes them suitable for non-operative treatment. 2,3 The treatment of choice has been a long-arm cast (LAC) with threepoint fixation following closed reduction. 3,4 The double sugar-tong splint (DSTS) is a long-arm plaster construct that prevents pronation-supination and limits flexionextension of the elbow, effective to provide threepoint fixation, with the advantage of reduced risk of compartment syndrome and can even be applied in presence of significant swelling where long arm cast is contraindicated.…”
Section: Introductionmentioning
confidence: 99%